2017
DOI: 10.1111/bor.12282
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoceanographic evolution of the SW Svalbard shelf over the last 14 000 years

Abstract: The palaeoceanographic evolution of the SW Svalbard shelf west of Hornsund over the last 14 000 years was reconstructed using benthic foraminiferal assemblages, stable oxygen and carbon isotopes, and grain‐size and ice‐rafted debris data. The results reveal the complexity of the feedbacks influencing the shelf environment: the inflow of Atlantic and Arctic waters (AW and ArW, respectively), and the influence of sea ice and tidewater glaciers. The inflow of subsurface AW onto the shelf gradually increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 78 publications
(225 reference statements)
1
18
1
Order By: Relevance
“…BP (Figure 5) may not result from the glacier advances and the blockage of the strait. The IRD values from Storfjorden and the Svalbard shelf west of Hornsund remained low in these periods (Nielsen and Rasmussen, 2018; Telesiński et al, 2018) and lake records have not revealed glacier advances in other regions of Svalbard (Allaart et al, 2021; de Wet et al, 2018; Røthe et al, 2015, 2018; Svendsen and Mangerud, 1997). In Hornsund, the radiocarbon dates of peat melted on the surface of Hansbreen suggest significant reduction in the glacier area around 7.9 and 5.9 ka cal.…”
Section: Discussionmentioning
confidence: 91%
“…BP (Figure 5) may not result from the glacier advances and the blockage of the strait. The IRD values from Storfjorden and the Svalbard shelf west of Hornsund remained low in these periods (Nielsen and Rasmussen, 2018; Telesiński et al, 2018) and lake records have not revealed glacier advances in other regions of Svalbard (Allaart et al, 2021; de Wet et al, 2018; Røthe et al, 2015, 2018; Svendsen and Mangerud, 1997). In Hornsund, the radiocarbon dates of peat melted on the surface of Hansbreen suggest significant reduction in the glacier area around 7.9 and 5.9 ka cal.…”
Section: Discussionmentioning
confidence: 91%
“…4). The YD is reflected in multiple records from the northeastern North Atlantic Ocean 7,8,19 . For instance, in Kveithola Trough located south of Storfjordrenna, the sea-ice proxy P III IP 25 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous marine sedimentary records attest that the northern hemisphere was subjected to rapid cooling over circa 1000 years during the YD 7,8 . As earlier investigations focused mainly on overviews of Late Glacial and Holocene paleoceanography of the Nordic Seas, the YD interval in marine records was presented in low temporal resolution (several hundreds of years).…”
mentioning
confidence: 99%
“…interpreted as a direct proxy of AW inflow, raised slowly and gradually (Figure 5). In comparison with the Greenland Sea record, in the northeastern Nordic Seas, the sSST (site M23258, Risebrobakken et al, 2011), as well as the abundance of AW indicators (site JM07-015, Telesiński et al, 2018), increased rapidly (Figure 5) indicating a maximum in AW advection already 10-11 ka BP (Husum and Hald, 2012;Risebrobakken et al, 2011). Shallow water (<50 m) temperatures around Svalbard were higher than at present (Mangerud and Svendsen, 2017) and AW reached the northern Svalbard shelf (Ślubowska-Woldengen et al, 2007), the northern Barents Sea (Berben et al, 2017) and as far as the western Fram Strait.…”
Section: Palaeoceanographic Reconstructionmentioning
confidence: 99%
“…Rasmussen and Thomsen, 2008, 2010) and the NAC flow along the Scandinavian, Barents Sea and Svalbard continental margins (e.g. Groot et al, 2014; Rasmussen et al, 2007, 2012, 2014; Ślubowska-Woldengen et al, 2007; Telesiński et al, 2018; Łącka et al, 2015, 2019) and/or through the Fram Strait into the Arctic Ocean (e.g. Aagaard-Sørensen et al, 2014; Spielhagen et al, 2011; Werner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%